Evaluasi Kinerja Terminal Induk Pal 6 Kota Banjarmasin - Bagus Priambodo Prima; Utami Sylvia Lestari (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
PAL 6 Main Terminal of Banjarmasin city is the type of terminal type B. The purpose of this study was to determine and analyze the operational PAL 6 Induk Terminal of Banjarmasin city at this time and know the performance of services provided by the terminal to the users, as well as the alternative of appropriate strategies to be executed so that the terminal can operate optimally. This Terminal Performance Evaluation is facilities to analyze variables by using Importance-Performance Analysis. The survey was conducted on the operating hours of the terminal as well as the location of the survey carried out in the PAL 6 Induk Terminal of Banjarmasin city. Surveys conducted surveying service facilities provided by the terminal to the user terminal and the interview survey questionnaires to the terminal users as much as 220 respondents. The survey questionnaire interviews in this study to own two types of questionnaires, the interests questionnaires, and satisfaction questionnaires. A questionnaire was addressed to stakeholders interests or terminal manager, while the performance or satisfaction questionnaire addressed to the user terminal. From the results, the IPA analysis obtained a concordance rate of (70.74%) while the performance or satisfaction questionnaire addressed to the terminal user. So that the overall performance of service quality according to the criteria of value Customer Satisfaction Index (CSI) is in a Good category.